Pharmacokinetics of fluconazole in cerebrospinal fluid and serum in human coccidioidal meningitis. - Tucker, R M (1988)
The pharmacokinetics of fluconazole, a new oral azole, were evaluated in cerebrospinal fluid and sera of eight patients with coccidioidal meningitis. At a dose of 50 mg/day, peak concentrations of 2.5 to 3.5 and 2.0 to 2.3 micrograms/ml occurred at 2 to 6 and 4 to 8 h in serum and cerebrospinal fluid, respectively. At 100 mg/day, peak concentrations of 4.5 to 8.0 and 3.4 to 6.2 micrograms/ml occurred at 2 to 4 and 4 to 12 h, respectively. The mean ratios of the concentration in cerebrospinal fluid to that in serum were 73.8% at 50 mg/day and 88.7% at 100 mg/day. Results suggested that there was a prolonged half-life in both cerebrospinal fluid and serum and that it was slightly longer in the former. Minimal toxicity was noted in 34 patient months of therapy (12 months on 50 mg daily; 22 months on 100 mg daily). After a mean of 4.5 months of therapy, five patients responded to therapy and three were unevaluable. The penetration of fluconazole into cerebrospinal fluid was substantial, toxicity was minimal, and early clinical experience was encouraging. Fluconazole holds promise as the sole or adjunctive therapy for fungal meningitis.